2017
DOI: 10.1016/j.chest.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

A Medical Student Perspective on Physician-Assisted Suicide

Abstract: Physician-assisted suicide and euthanasia (PAS/E) has been increasingly discussed and debated in the public arena, including in professional medical organizations. However, the medical student perspective on the debate has essentially been absent. We present a medical student perspective on the PAS/E debate as future doctors and those about to enter the profession. We argue that PAS/E is not in line with the core principles of medicine and that the focus should be rather on providing high-quality end-of-life a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…According to a medical student's perspective, euthanasia and assisted suicide are not in line with the core principles of medicine and that the focus should be rather on providing high-quality end-of-life and palliative care. 13 In Germany, the majority of students surveyed wrongly assumed that assisted suicide was a punishable offense, although most of them considered assisted suicide ethically acceptable, compared to euthanasia. 14 Study limitations of this survey include the convenience sample and the incomplete list of physicians existing in Italy interviewed.…”
Section: Commentmentioning
confidence: 99%
“…According to a medical student's perspective, euthanasia and assisted suicide are not in line with the core principles of medicine and that the focus should be rather on providing high-quality end-of-life and palliative care. 13 In Germany, the majority of students surveyed wrongly assumed that assisted suicide was a punishable offense, although most of them considered assisted suicide ethically acceptable, compared to euthanasia. 14 Study limitations of this survey include the convenience sample and the incomplete list of physicians existing in Italy interviewed.…”
Section: Commentmentioning
confidence: 99%
“…Similar results were obtained in a study conducted in Germany, which demonstrated that both in 2004, and 12 years later in a 2016 study, only a small proportion of students supported the legalization of euthanasia and assisted suicide, possibly indicating that as future physicians they would not be able to perform such an operation on a patient [33]. Another study that examined the views of future physicians also found that medical students do not support euthanasia because it is contrary to the principles of medicine to care for patients by using the available options of medicine and palliative care and to provide them with a dignified death [34].…”
Section: Discussionmentioning
confidence: 99%
“…A maioria dos estudos sobre aceitação do suicídio assistido por médico conduzidos com estudantes de medicina apresenta uma proporção crescente de estudantes que aceitam a eutanásia como possível solução em condições terminais, embora a maioria continue se posicionando contra a prática 7,8 . Além disso, muitos argumentam que o suicídio assistido por médico está em desacordo com princípios éticos fundamentais e que os cuidados paliativos poderiam ser uma solução para lidar com esses pacientes 9 .…”
unclassified